The Role of Corporate Governance and Financial Performance on the Value of ISSI Indexed Food and Beverage Companies in Indonesia - Rahma, Sukma Aulia; Nur, Silva Maulida; Anggraini, Devi Dwi; Kunasari, Kunasari; Andni, Riyan; Sironi, Manuela (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
This study comprises food and beverage firm listed on the ISSI index for the year 2017 through 2021 and is driven by the impact of corporate governance and financial performance on company value on the Indonesia Stock Exchange (IDX). The purpose of this study was to investigate the relationship between financial success measured by ROA (return on Asset) and ROE (Return on Equity) and Managerial Ownership (MO), Institutional Ownership (IO), Independent Commissioners (IC), and Audit Commissioners (AC), all of which are factors in good corporate governance. The methode used is quantitative axplanatory using multiple linear regression analysis and sampling using purposive sampling with reference to the two theories applied to research which consist of planned signaling theory and agency relationship theroy. There is the application of Good Corporate Governance in the analysis of a company’s finances and there are important components in the form of Return of Asset (ROA), Return of Equity (ROE), Good Corporate Governance and Financial Performance, according to Managerial Ownership (MO), Institutional Ownership (IO), Independent Commissioners (IC), and the Audit Committee (AC), can enhance a company’s worth. Despite having a favorable impact and not being statistically significant, return on assets, managerial ownership, institutional ownership, and independent commissions all have positive effects.